2008
DOI: 10.1162/evco.2008.16.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Immune Algorithm with Nondominated Neighbor-Based Selection

Abstract: Nondominated Neighbor Immune Algorithm (NNIA) is proposed for multiobjective optimization by using a novel nondominated neighbor-based selection technique, an immune inspired operator, two heuristic search operators, and elitism. The unique selection technique of NNIA only selects minority isolated nondominated individuals in the population. The selected individuals are then cloned proportionally to their crowding-distance values before heuristic search. By using the nondominated neighbor-based selection and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
223
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 448 publications
(226 citation statements)
references
References 21 publications
0
223
0
3
Order By: Relevance
“…Simulated binary crossover (SBX) is one of the main recombination operators used in various real-coded, multi-objective optimization algorithms (Deb et al 2002;Gong et al 2008). In this paper, the SBX operation is performed on the population before and after the application of the proportional clonal operation, which is similar to the operation used in Deb et al, 2002 andGong et al, 2008. The operation can be described as follows:…”
Section: Recombination Operatormentioning
confidence: 99%
See 2 more Smart Citations
“…Simulated binary crossover (SBX) is one of the main recombination operators used in various real-coded, multi-objective optimization algorithms (Deb et al 2002;Gong et al 2008). In this paper, the SBX operation is performed on the population before and after the application of the proportional clonal operation, which is similar to the operation used in Deb et al, 2002 andGong et al, 2008. The operation can be described as follows:…”
Section: Recombination Operatormentioning
confidence: 99%
“…By using non-dominated neighbor-based selection and proportional cloning, the method enhances the local search results in the lesscrowded regions of the current trade-off front. The experimental study showed that NNIA converges on the true Pareto optimal fronts when solving most test problems and is much better than the other algorithms, such as SPEA2, NSGA-II, PESA-II, and MISA (Gong and Jiao 2008). However, the probability of being trapped in the local optima of multimodal problems when using this algorithm is increased significantly.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the past 10 years, a number of artificial immune model-based multi-objective optimization algorithms have been proposed, including the evolutionary multi-objective immune algorithm [45], the non-dominated neighbor immune algorithm [51], the weight-based multi-objective artificial immune system [52], and the novel immune clonal algorithm (NICA). Experiments have demonstrated that among the existing algorithms, the quality of non-dominated solution sets obtained using the NICA is, in most cases, far superior to that obtained using other algorithms [32].Therefore, the present study uses the NICA as an essential method for solving the multi-objective LUA optimization problems.…”
Section: Design Of the Multi-objective Optimization Algorithmmentioning
confidence: 99%
“…Based on this, we implement four classical MO-AIS algorithms, CLONA LG [11], NNIA [12], MISA [13] and CM OIA [14], to show the validity of this framework. …”
Section: Introductionmentioning
confidence: 99%